ARTOWARDS THE HEALTHY CITY : A REFLECTION ON PLANNING FOR HEALTH - Neil Whittingham (NALARs, 2012)
ABSTRACT. Health, in a sense, can be considered an intensely personal matter, strongly governed by behavioural choices and genetics. However, indicators show that at the level of the community or the city, marked disparities exist in morbidity and mortality throughout the world. Clearly, politics, economics and geography also have a bearing on health outcomes, and not just in environments that are obviously extremely hazardous. Health problems can in part be due to a failure to reconcile the impact of the layout and design of urban form with the needs of individuals and communities for space to achieve a healthy existence. This article seeks a greater understanding of how the planning, design and management of cities have a bearing on sustainable development and the health of their citizens. It seeks such an understanding through a consideration of the social and environmental determinants of health and the influence that urban policy has upon the quality or liveability of cities. Lessons are sought from development theory and the move towards more collaborative approaches to health, looking particularly at the WHO Healthy Cities Project, to identify challenges and recommendations for future policy. Key words: health, wellbeing, sustainable development, urban planning, collaboration, WHO Healthy Cities Project.  ABSTRAK. Kesehatan dapat dikatakan sebagai masalah pribadi, yang biasanya merupakan akibat genetika ataupun pilihan kebiasaan. Namun, indicator-indikator memperlihatkan bahwa pada tingkat masyarakat atau kota tertentu, terdapat kesenjangan dalam morbiditas dan mortalitas di seluruh dunia. Jelasnya, politik, ekomoni dan geografi juga memiliki pengaruh pada luaran kesehatan, tidak hanya pada lingkungan tertentu yang sangat jelas berbahaya. Masalah kesehatan sebagian disebabkan karena adanya kegagalan dari akibat tata ruang dan disain dari “urban form” disesuaikan dengan kebutuhan individu dan komunitas akan ruang untuk mencapai kehidupan yang lebih sehat. Artikel ini bertujuan untuk mencari pemahaman yang lebih besar dari bagaimana perencanaan, disain dan pengelolaan sebuah kota yang memiliki pengaruh pada pembangunan berkelanjutan dan masyarakat yang sehat. Selain itu juga untuk mencari pemahaman seperti melalui pertimbangan faktor penentu sosial dan lingkungan kesehatan dan pengaruh bahwa kebijakan perkotaan ditentukan oleh kualitas atau kelayakan sebuah  kota. Pelajaran dicari dari teori pengembangan dan pergerakan menuju pendekatan yang lebih kolaboratif untuk kesehatan, terutama dengan melihat Proyek Kota Sehat dari WHO, untuk mengidentifikasikan tantangan dan rekomendasi bagi kebijakan masa depan.      Kata kunci: kesehatan, pengembangan berkelanjutan, perencanaan kota, kolaborasi, Proyek Kota Sehat WHO